Overheid en godsdienst: een moeizame relatie - Rouvoet, André (Religie & Samenleving, 2012)
In Dutch society freedom of religion has a long standing tradition and is constitutionally well guaranteed. The recent public and political discussion on e.g. ritual slaughter, wearing religious symbols in public, freedom of education, the prohibition of blasphemy, however points at a growing intolerance among the secular majority considering some of the aspects of freedom of religion out of date. The author, a christian democrat and former minister of Youth and Family, analyses the causes of this change and makes a plea for a fundamental reluctance whenever limitation of a constitutional right like freedom of religion is at stake.